Ethnomedicinal plants : a biodiversity treasure - Mohan, V. R., 1959- (Daya Publishing House, a division of Astral International Pvt. Ltd., 2018)
"At first fleeting look, "Ethnomedicinal Plants: A Biodiversity Treasure" appears to be a medicinal compendium of plants intended as a guide and reference resource for professionals in the field. Anyone who picks up this book, it contains nuggets of information that would interest a great many readers, from school children to teachers, from undergraduates to researchers, from homemakers to business people and of course, the healthcare professionals..." -- Provided by publisher.